KAJIAN BISOSIASI PADA KISAH HUMOR SI KABAYAN DAN ABU NAWAS SEBAGAI SEBUAH ALTERNATIF PEMBELAJARAN SASTRA - Yudha Andana Prawira (Tatar Pasundan : Jurnal Diklat Keagamaan, 2019)
The problem in this study is to compare the humorous aspects of Si Kabayan's story with Abu Nawas and describe it according to the objectives of the research. The research method is qualitative with Koestler's psychological methods with applications in bisociation. The results of this study show similarities and differences between the characters in Si Kabayan's story with Abu Nawas. The main equation is that the sense of humor is high because of the large gap between the M1 and M2 levels of each story. Similarly, motives and mandates are similar to the ingenuity aspects used to deceive others. At the same time, the difference lies in the fact that Si Kabayan has a socio-cultural origin from the lower classes of Sundanese society. While Abu Nawas has a Middle Eastern culture with a social environment around the palace. Both stories are full of irony and paradox in the real life of each region. Key words: Si Kabayan; Abu Nawas; humor; criticism; paradox